Evaluation of vetiver and coco coirnet as soil erosion and runoff barriers at Tanay, Rizal - Pintor, Eleanor M. (Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2007)
The claimed benefits of biological barriers, particularly those of vetiver and coco coirnet were studied at two micro-watershed areas in the Tanay National Soil and Water Resources Research Development Center (TNSWRRDC) Tanay, Rizal. These barrier materials were applied on two set-ups, on grassland and on plots with farming intervention, Each set-up had a control erosion plot, plot planted with vetiver, plot planted with vetiver combined with coco coirnet and plot installed with coco coirnet. Plots with farming activities have existing madre de cacao (Gliricidia sepium) and pineapple.